Ni(II) Salt-catalyzed Direct Aryl Thioetherification of 1-Naphthylamine and Its Derivative with Disulfides - Jiang, Chunfeng; Liu, Kaixuan; Zhang, Le; Liu, Tian; Zhang, Nan; Xu, Youjun (Chemistry letters, 2022)
The direct C-H aryl thioetherification of 1-naphthylamine and its derivative with diaryl disulfides was developed with a Ni(II) salt catalytic system under air. The protocol was compatible with a wide range of functional groups. 1-Naphthylamine and 1,2,3,4-tetrahydro-1-naphthylamine were converted into various aryl sulfide compounds under standard conditions. The application of the proposed methodology to prepare some highly-functionalized small molecules as building blocks for bioactive compounds was explored. Control experiments revealed the Ni(II)/Ni(IV) cyclic mechanism of the catalytic system.